2004
DOI: 10.1111/j.1469-8986.2004.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and skin conductance analysis of antecendents and consequences of decision making

Abstract: The current study examined the pattern of heart rate and skin conductance changes preceding risky choices and following outcome for bad, moderate, and good performers on an analogue of the Iowa gambling task (Bechara, Damasio, Damasio, & Anderson, 1994). The task required a choice between four options; two options were followed by a high reward and, unpredictably, an even higher loss (disadvantageous options) and two other options were followed by a small reward but the unpredictable loss was also small (advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
175
4
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(211 citation statements)
references
References 31 publications
24
175
4
4
Order By: Relevance
“…Reponses were made approximately 500-1000ms following the countdown end, resulting in an intertrial interval of approximately 8 seconds. These timings were similar to studies by Bechara et al (1996), Damasio (2002), andCrone et al (2004). …”
supporting
confidence: 73%
See 1 more Smart Citation
“…Reponses were made approximately 500-1000ms following the countdown end, resulting in an intertrial interval of approximately 8 seconds. These timings were similar to studies by Bechara et al (1996), Damasio (2002), andCrone et al (2004). …”
supporting
confidence: 73%
“…These findings appear contrary to the assumption that decision-making performance depends on the development of anticipatory SCRs, and suggests that appraisal Autonomic arousal during good and bad decisions 5 physiology underlie individual differences in decision-making. Conversely, Crone et al (2004) found autonomic activity during appraisal to be independent from performance strategy, while heart rate slowing and SCL were greater preceding selections from bad but not good decks.Tomb, Hauser, Deldin and Caramazza (2002) further challenge the notion that somatic states act to mark the long-term consequences of decisions. They propose that high magnitude physiological responses are elicited when healthy participants anticipate bad decks, because bad decks yield rewards and punishments of high magnitude compared to good decks.…”
mentioning
confidence: 95%
“…Previous studies also indicate that in adolescents, developmental improvements in the IGT performance could not be explained by developmental changes in working memory capacity and inductive reasoning Hooper et al, 2004;Overman et al, 2004). Indeed, adolescents are often capable of explaining reward probabilities, despite making disadvantageous decisions (Crone, Jennings et al, 2004;Crone, Somsen et al, 2004). Many aspects of adolescent cognitive functions have been shown to be equivalent to those of adults under laboratory situations, but they show greater deterioration under more real-life, stressful conditions (Steinberg, 2004); adolescents with well-developed decision-making abilities demonstrated under non-emotional conditions seem to have a much more difficult time making a responsible choice under intense emotional arousal (Arnsten & Shansky, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Developmental studies have suggested that maturation of the OFC/VMPC, might be a developmentally distinct process from maturation of other regions of the frontal lobe Hooper et al, 2004). Other studies have shown that adolescents make disadvantageous decisions, yet they seem to have a mature capacity to reason and to explain reward probabilities (Crone, Jennings, & Van der Molen, 2004;Crone, Somsen, Van Beek, & Van Der Molen, 2004). Therefore, we anticipate that poor decision-making in binge drinkers is not due to deficits in their "cold" dorsolaterally mediated executive functions, and thus we expect normal scores on working memory and school academic performance, but poor performance on the original version of the IGT.…”
Section: Introductionmentioning
confidence: 99%
“…Two decks are advantageous, yielding a net profit (termed the safe or good decks); the other two decks deliver a net loss (termed the risky or bad decks). Bechara et al (1997) found that EDA is higher before choices from risky decks than choices from safe decks (for replications, see, e.g., Bechara, Damasio, Damasio, & Lee, 1999; Crone, Somsen, Van Beek, & Van Der Molena, 2004; Tchanturia et al, 2007). The IGT tests decision making under ambiguity, and requires learning the reward contingencies of the four decks through trial and error.…”
mentioning
confidence: 99%